Carbon Sequestration in Two Created Riverine Wetlands in the Midwestern United States. Issue 4 (1st July 2013) - Bernal, Blanca; Mitsch, William J.
Abstract : Wetlands have the ability to accumulate significant amounts of carbon (C) and thus could provide an effective approach to mitigate greenhouse gas accumulation in the atmosphere. Wetland hydrology, age, and management can affect primary productivity, decomposition, and ultimately C sequestration in riverine wetlands, but these aspects of wetland biogeochemistry have not been adequately investigated, especially in created wetlands. In this study we investigate the ability of created freshwater wetlands to sequester C by determining the sediment accretion and soil C accumulation of two 15‐yr‐old created wetlands in central Ohio—one planted and one naturally colonized. We measured the amount of sediment and soil C accumulated over the parent material and found that these created wetlands accumulated an average of 242 g C m −2 yr −1, 70% more than a similar natural wetland in the region and 26% more than the rate estimated for these same wetlands 5 yr before this study. The C sequestration of the naturally colonized wetland was 22% higher than that of the planted wetland (267 ± 17 vs. 219 ± 15 g C m −2 yr −1, respectively). Soil C accrual accounted for 66% of the aboveground net primary productivity on average. Open water communities had the highest C accumulation rates in both wetlands. This study shows that created wetlands can be natural, cost‐effective tools to sequester C to mitigate the effect of greenhouse gas emissions.